Impact of initial bulk-heterojunction morphology on operational stability of polymer:fullerene photovoltaic cells - Kim,J-S (Advanced Materials Interfaces, 2019)
Controlling initial bulk-heterojunction (BHJ) morphology is critical for device performance of organic photovoltaic (OPV) cells. However, its impact on performance, specifically long-term operational stability is still poorly understood. This is mainly due to limitations in direct measurements enabling in-situ monitoring of devices at a molecular level. Here, we utilize thermal annealing preconditioning step to tune initial morphology of model polymer:fullerene BHJ OPV devices and molecular resonant vibrational spectroscopy to identify in-situ degradation pathways. We report direct spectroscopic evidence for molecular-scale phase segregation temperature (TPS) which critically determines a boundary in high efficiency and long operational stability. Under operation, initially well-mixed blend morphology (no annealing) shows interface instability related to the hole-extracting PEDOT:PSS layer via de-doping. Likewise, initially phase-segregatedmorphology at a molecular level (annealed above TPS) shows instability in the photoactive layer via continuous phase segregation between polymer and fullerenes in macroscales, coupled with further fullerene photodegradation. Our results confirm that a thermal annealing preconditioning step is essential to stabilize the BHJ morphology; in particular annealing below TPS is critical for improved operational stability whilst maintaining high efficiency.